Medical shifts passage as a management tool for patient safety - Juliana da Silva Garcia Nascimento; Regina Rodovalho Rodrigues; Fabiana Cristina Pires; Bárbara Ferreira Gomes (Universidade Federal de Santa Maria, 2018)
Objective: to understand the nurses' shift process and to develop a tool to scientifically enable such context. Method: a qualitative, descriptive study, carried out with 18 nurses, through semi-structured interviews analyzed by the Content Analysis, from September to December 2016. For the instrument elaboration, participant observation and the Method of the Arch of Maguerez were used. Results: it was identified that the passage of the shift is empirical, evidencing the absence of a scientific tool that qualifies this process, which weakens patient safety. Critical nodes were detected, such as: the location of the shift, interruptions and over-communication, thus, an instrument was developed as a checklist format based on the Situation, Background, Assessment, Recommendation - SBAR model of communication. Final considerations: it is evident that it is possible to eliminate the empirical character of the shift by using the SBAR tool, which benefits patient safety.